Serum levels of adiponectin, CCL3/MIP-1α, and CCL5/RANTES discriminate migraine from tension-type headache patients - Renan B. Domingues; Halina Duarte; Carlos Senne; Gustavo Bruniera; Fernando Brunale; Natália P. Rocha; Antonio L. Teixeira (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objectives Inflammatory molecules and neurotrophic factors are implicated in pain modulation; however, their role in primary headaches is not yet clear. The aim of this study was to compare the levels of serum biomarkers in migraine and tension-type headache. Methods This was a cross-sectional study. We measured serum levels of adiponectin, chemokines, and neurotrophic factors in patients with migraine and tension-type headache. Depression and anxiety symptoms, headache impact and frequency, and allodynia were recorded. Results We included sixty-eight patients with migraine and forty-eight with tension-type headache. Cutaneous allodynia (p = 0.035), CCL3/MIP-1α (p = 0.041), CCL5/RANTES (p = 0.013), and ADP (p = 0.017) were significantly higher in migraine than in tension-type headache. The differences occurred independently of anxiety and depressive symptoms, frequency and impact of headache, and the presence of pain. Conclusions This study showed higher CCL3/MIP-1α, CCL5/RANTES, and ADP levels in migraine in comparison with tension-type headache. Our findings suggest distinctive roles of these molecules in the pathophysiology of these primary headaches.